Evaluation of resistance sourses in cassava germplasm to Xanthomonas campestris pv. manihotis in Santa Catarina, Brazil. - Miura, Lucas; Frosi, Jandir Francisco; Mondardo, Euclides; Ternes, Murito (Pesquisa Agropecuaria Brasileira, 2014)
Cassava germplasm screening to bacterial blight resistance, Xanthomonas campestris pv. manihotis (Xcm) was held in Santa Catarina, Brazil. Four hundred and sixty-one genotypes, including 163 from the states of Sta. Catarina and Rio Grande do Sul and 298 from CNPMF were tested. From the last material, 92 were from Germplasm Bank (BG), 167 from CIAT, Colombia (CPM), 34 from CNPMF (clone) and 5 from CNPMF which identification has been lost (SN). The experiments were realized in 1977, 78, 79, 80, 81, 82 and 83 in four distincts localities: Itajaí, Agrolândia, Pouso Redondo (1 year) and Jaguaruna. From the genotypes selected as promising, 13 were from Sta. Catarina and Rio Grande do Sul, 20 from 80,20 from CPM, 7 from CNPMF and one from SN.